When specific exercise is more effective than medication - Sensorimotor training is currently the most promising option to treat and prevent chemotherapy-induced peripheral neuropathy (CIPN). - Fiona Streckmann; Maryam Balke; Céline Hammadou; Bianca Schmidli; Oliver Faude; Sarah Koch (Current Issues in Sport Science)
Introduction Chemotherapy-induced peripheral neuropathy (CIPN) is a highly prevalent and clinically relevant adverse effect of chemotherapy, negatively impacting patient quality of life. The lack of effective preventive or therapeutic options regarding CIPN often requires changes in cancer therapy, potentially resulting in reduced survival. Meanwhile 10 studies have shown that specific exercise can reduce relevant symptoms of CIPN (Streckmann eu al. 2021). In our most recent study (Streckmann et al. 2024) we have been able to show that CIPN can even be prevented by up to 70%.